Perputaran Kas, Perputaran Piutang Dan Modal Intelektual Meningkatkan Kinerja Keuangan Pada Perusahaan Sub Sektor Makanan Dan Minuman - Fitrianingsih, Dwi; Fidziah, Fidziah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of Cash Turnover, Accounts Receivable Turnover, and Intellectual Capital on Financial Performance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2020–2024. The findings of this study are expected to provide insights for stakeholders regarding the roles of Cash Turnover, Accounts Receivable Turnover, and Intellectual Capital in business operations, thereby creating added value and competitive advantage amid business competition. Furthermore, the study is also expected to offer a general overview of corporate financial performance, which is measured using Return on Assets (ROA). The study involves 55 companies selected through purposive sampling. The data analysis method used is multiple linear regression. The results indicate that Cash Turnover has a significant effect on Return On Assets (ROA), while Accounts Receivable Turnover does not have a significant effect. On the other hand, Intellectual Capital has a significant effect on ROA. Simultaneously, the three variables, Cash Turnover, Accounts Receivable Turnover, and Intellectual Capital significantly influence the financial performance of the companies as measured by Return On Assets (ROA).